2017
DOI: 10.1186/s12886-017-0516-1
|View full text |Cite
|
Sign up to set email alerts
|

Calculation of iris-claw IOL power for correction of late in-the-bag IOL complex dislocation

Abstract: BackgroundTo assess the constants and formula for aphakia correction with iris-claw IOLs to achieve the best refractive status in cases of late in-the-bag IOL complex dislocation.MethodsA literature search was performed. The following data were obtained: Iris-claw IOL model, Iridal or retroiridal enclavation, A-constant, ultrasound or optical biometry, formula employed and refractive outcomes. Acceptable emmetropia was considered if the resulting spherical equivalent (SE) was within ±1.00 D.ResultsThe majority… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 43 publications
0
8
0
1
Order By: Relevance
“…In an overview of studies addressing IOL calculation in iris‐claw implantation, Huerva et al. (2017) reported that in approximately 80% of the studies involving retropupillary iris‐claw lens, the SRK‐T formula had been used, of which 60% had achieved a spherical equivalent (SE) within ± 1.0 D using different A‐constants (i.e. 116.7–117.5).…”
Section: Postoperative Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In an overview of studies addressing IOL calculation in iris‐claw implantation, Huerva et al. (2017) reported that in approximately 80% of the studies involving retropupillary iris‐claw lens, the SRK‐T formula had been used, of which 60% had achieved a spherical equivalent (SE) within ± 1.0 D using different A‐constants (i.e. 116.7–117.5).…”
Section: Postoperative Resultsmentioning
confidence: 99%
“…Because many such surgeries involve aphakic eyes or eyes with dislocated IOLs, newer IOL formulas are infeasible, and in most studies, the SRK-T formula has therefore been used. In an overview of studies addressing IOL calculation in iris-claw implantation, Huerva et al (2017) reported that in approximately 80% of the studies involving retropupillary iris-claw lens, the SRK-T formula had been used, of which 60% had achieved a spherical equivalent (SE) within AE 1.0 D using different A-constants (i.e. 116.7-117.5).…”
Section: Prediction Errormentioning
confidence: 99%
“…Interestingly, the refractive results observed in our series support the benefits of performing a tunnelized scleral incision to reduce the induced astigmatism compared with corneal incision, a modification of the original technique advocated in previous reports. [21][22][23] Elevations in IOP were frequent, and half of the study cohort presented an IOP .21 mmHg at some point during follow-up (cumulative probability of 48.1% at 12 months). The clinical impact of these elevations was, however, mild because this was successfully managed with IOP-lowering drops in most cases.…”
Section: Discussionmentioning
confidence: 99%
“…63,64 In addition, 4 editorials and 10 reviews mainly or partly discussed late in-the-bag IOL dislocation. 28,[65][66][67][68][69][70][71][72][73][74][75][76][77] A number of articles were excluded because they contained less than 50% or an unknown proportion with the condition, although 1 of these articles reported some results separately for in-the-bag IOL dislocation. 30…”
Section: Resultsmentioning
confidence: 99%